Soils and vegetation of the riverside floodplain in the hydrological continuum of the southern tundra within the Pur-Taz interfluve (Western Siberia) - Loiko, Sergey V.; Klimova, Nina V.; Kritskov, Ivan V.; Kuzmina, Daria M.; Kulizhsky, Sergey P. (Acta biologica sibirica)
Climate warming has significantly impacted the ecosystems of the Subarctic and Arctic. It has most strongly affected highly productive ecosystems, including those formed in river floodplains. Due to the initially high (background) values of NDVI, remote monitoring methods are not suitable for detecting changes in the biological productivity of floodplain vegetation. Research for both individual regions and landscapes is needed. However, for the floodplains of many rivers in Western Siberia, there are no primary descriptions of soils and vegetation. We have studied the soils and vegetation of the riverside floodplains in the lower reaches of the Taz River within the Pur-Taz interfluve. The studies were carried out within the hydrological continuum from the stream to the main Taz River. A regular change in soils and vegetation along the hydrological continuum was established, with fluvial processes intensifying. Ecosystems with the greatest diversity of plants, with thick layered soils such as Pantofluvic Fluvisol (Polyarenic, Polysiltic, Humic), are formed in the valleys of the tributaries of the Taz River on the natural riverside levee. The floodplain of the Taz River is distinguished by small differences in the heights of topographic elements, loamy soil texture, waterlogging and permafrost. The soils of the studied hydrological continuum were assigned to two Reference Soil Groups (Gleysol and Fluvisol). To describe the diversity of basic soil properties, six principal qualifiers and nine supplementary qualifiers were used. An assumption was made about the replacement of willow bushes by alder bushes during the warming period with the growth of some species of forbs (Parasenecio hastatus). The study made it possible to outline ways of further studying the floodplains of the Subarctic of Western Siberia.